Facilitating the interpretation of the multidimensional EORTC QLQ-FA12 fatigue questionnaire: establishing thresholds for clinical importance - Blickle, Patricia; Storz, Lisa M.; Schmidt, Martina E.; Lehmann, Jens; Pilz, Micha J.; Milzer, Marlena; Maatouk, Imad; Giesinger, Johannes M.; Steindorf, Karen (European journal of cancer, 2026)
Objective - Cancer-related fatigue is among the most burdensome side-effects of cancer and its treatment. The Fatigue Questionnaire of the European Organization for Research and Treatment of Cancer (EORTC QLQ-FA12) is a widely used measure to assess fatigue multidimensionally. However, interpretation of its scores can be challenging. Therefore, thresholds for clinical importance (TCI) for the three fatigue dimensions assessed by this questionnaire were developed. - Methods - A standardized approach was followed for the derivation of TCI. Three anchor items regarding limitations in daily life, need for help/care, and worries to the patient, their partner and/or family were completed by patients with various cancer types, in addition to the EORTC QLQ-FA12. Receiver Operating Characteristic curves and Youden's J were estimated to determine the most suitable TCIs. - Results - Complete data of the EORTC QLQ-FA12 and the anchor items were available for N=1111 patients (age 67.2±12.6 years; 61.2% female) from two observational studies. The derived TCIs for the physical, emotional, and cognitive fatigue scores (scale 0-100) were 43, 28, and 25, respectively. Subgroup analyses, categorized by gender and age, yielded consistent results. The sensitivity of the thresholds ranged from 0.87 to 0.94; the specificity from 0.67 to 0.80. Areas under the curve were all ≥0.89. - Conclusion - The analyses established TCIs for the three dimensions of the EORTC QLQ-FA12. TCIs can be used in research and clinical practice to facilitate interpretation of individual patient scores at a single point in time. TCIs may indicate which patients experience a fatigue level that warrants additional clinical attention.